2015
DOI: 10.1089/neu.2014.3492
|View full text |Cite
|
Sign up to set email alerts
|

Early Cortical Thickness Change after Mild Traumatic Brain Injury following Motor Vehicle Collision

Abstract: In a motor vehicle collision (MVC), survivors often receive mild traumatic brain injuries (mTBI). Although there have been some reports of early white matter changes after an mTBI, much less is known about early cortical structural changes. To investigate early cortical changes within a few days after an MVC, we compared cortical thickness of mTBI survivors with nonmTBI survivors, then reexamined cortical thickness in the same survivors 3 months later. MVC survivors were categorized as mTBI or non-mTBI based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 70 publications
3
48
4
Order By: Relevance
“…11 Their study found cortical thinning in the left middle temporal gyrus at baseline, but much less extensive than what was observed in the current study. In addition, their study reported significant cortical thickening in the mTBI group in the right precuneus and the left rostral middle frontal gyrus.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…11 Their study found cortical thinning in the left middle temporal gyrus at baseline, but much less extensive than what was observed in the current study. In addition, their study reported significant cortical thickening in the mTBI group in the right precuneus and the left rostral middle frontal gyrus.…”
Section: Discussioncontrasting
confidence: 72%
“…10 Another recent study, based on 21 patients with mTBI from motor vehicle collisions, found cortical thinning in the left posterior middle temporal gyrus and cortical thickening in the right precuneus and left rostral middle frontal gyrus in the acute phase after injury. 11 In light of these findings, changes in cortical thickness appear to be a pathologic feature in mTBI.…”
Section: Introductionmentioning
confidence: 98%
“…In a pilot study, Wang et al [27] observed alterations in cortical thickness at an early stage after MTBI. Thus, the frontal cortical structures may change dynamically over the initial 3 months after injury.…”
Section: Discussionmentioning
confidence: 99%
“…Some longitudinal studies have described the development of atrophy after MTBI [23][24][25][26][27][28]. In contrast, two other studies observed no atrophy in patients diagnosed with MTBI [16,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation